(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Heart failure (HF) is a major and still growing medical and economic problem with significant morbidity and mortality. Industrialized countries spend 1–2% of their healthcare budgets on HF care, and most costs are attributable to HF hospitalizations. Heart Logic is an advanced diagnostic tool designed to provide early detection of worsening heart failure. Integrated into implantable cardiac devices, Heart Logic utilizes multiple physiological and electrical parameters—including heart sounds, respiratory rate, thoracic impedance, heart rate variability, and activity levels—to generate a composite index that reflects a patient’s heart failure status. By continuously monitoring these metrics, Heart Logic offers predictive alerts that enable clinicians to proactively manage heart failure, reducing hospitalizations and improving patient outcomes. Clinical studies have demonstrated its effectiveness in detecting heart failure decompensation weeks in advance, allowing timely intervention. This tool represents a significant step forward in remote patient monitoring, enhancing both patient care and healthcare efficiency.